Effect of Mancozeb on Thyroid, Testis, Accessory Reproductive Organs and Biochemical Constituents in Albino Mice - B. Kaliwal2*, Raghavendra L. Ksheerasagar1 and Basappa (Recent Research in Science and Technology, 2010)
Abstract Mancozeb, a fungicide of ethylenebisdithiocarbamate group was orally administered at doses of 200, 400, 600 and 800 mg/kg/ day to male swiss albino mice for 30 days. Daily body weights of the mice were recorded and the mice were sacrificed on the 31st day. Testes weight decreased significantly in all the mancozeb treated mice except 200 mg/kg/ day treated mice. Mice treated with 600 and 800 mg/kg/ day showed significant decrease in the number and diameter of spermatogenic cells and Leydig cells. However, treatment with 600 mg/kg/ day revealed no significant change in the diameter of spermatogonia and primary spermatocytes. Histological studies of the testis of the mice treated with high doses of mancozeb revealed spermatogenesis inhibition reflected by significant decrease in number of spermatogenic cells and sperms. The thyroid effect of mancozeb is revealed by the number of small follicles decreased where as the number of medium and large follicles increased significantly with hypertrophy and hyperplasia of follicular cells with loss of colloid in mice treated with high doses of mancozeb when compared with corresponding parameters of control. Mice treated with 800 mg/kg/ day mancozeb showed significant decrease in the weight of prostate and Cowper’s glands. Mice treated with 600 and 800 mg/kg/ day mancozeb showed significant decrease in the kidney, spleen and liver weight, where as thyroid weight increased significantly. However, thymus weight increased significantly in the mice treated with 600 and 800mg/kg/ day mancozeb. Mice treated with 200 and 400 mg/kg/ day mancozeb caused no significant change in the biochemical constituents in testes, liver and kidney. However treatment with 600 mg/kg/ day mancozeb caused significant decrease in the level of protein in liver and glycogen in the liver and kidney and a significant increase in the level of total lipids in testis. Treatment with 800 mg/kg/ day mancozeb caused significant decrease in the levels of protein and glycogen and significant increase in the level of total lipids in the testis and liver and a significant decrease in the protein, glycogen and total lipids in the kidney. These observed effects of mancozeb on testis, thyroid and biochemical constituents may be due to hormonal imbalance in any of the stages in the hypothalamo-hypophysial-testicular axis or hypothalamo – hypophysial –thyroid axis. Keywords: Mancozeb, Testis, Thyroid, Mice, Toxicity